Pengembangan Media Buku Cerita BergambarUntuk Meningkatkan Keterampilan BahasaAnak Usia Dini di DKI Jakarta - Yudrik Jahja; Yasmin Paradiba (Publikasi Indonesia, 2022)
Early Childhood Education (ECE) is the level of education before the level of basic education which is an effort of guidance that is shown for children aged 0-6 years which is done through providing educational stimuli, to help the growth and development of physical and spiritual so that children have readiness in entering further education. Speaking is closely related to language development which is acquired by children through listening, listening, and storytelling activities. Children can speak well because they have sufficient language vocabulary, and are able to express it. Language development in children is carried out by using learning media as a supporting tool. In line with the previous opinion Hadders-Algra said that, through media, early childhood will be easier to present abstract understanding into a more concrete understanding. That way, learning media is one of the most important parts of the learning process because it can facilitate limited understanding. Therefore, based on the problems and obstacles that exist in the field, the researchers tried to solve the problem by developing picture storybook media. The purpose of this study is to invite teachers/educators to motivate children to speak through storybook reading activities. The goal to be achieved in this study is that teachers/educators can create and express ideas in making a children's story based on existing themes. In this study, the research method of developing picture storybook media, using the ADDIE development model developed by Cennamo, Abell & Chung, that the development procedure starts from the Analysis, Design, Development, Implementation, Evaluate stages. Meanwhile, according to Sezer et al, states that the ADDIE model is the system approach implies an analysis of how the components of all phases. This opinion can be interpreted that the ADDIE model is an approach that emphasizes an analysis of how each component interacts with each other in coordination with the existing phases. This research was conducted in several PAUDs in the DKI Jakarta area.